Effectiveness of Flipped Classroom–Based Instruction for Developing Arabic Reading Skills - Lalu Maulana Malik; Bakri Muhammad Bakhit; Dewi Chamidah (Nurul Jadid University, 2025)
Reading skill (maharatul qirā’ah) is a fundamental component of Arabic language learning, yet many students experience difficulties due to limited vocabulary mastery and low reading fluency. This study aims to determine the effectiveness of the “flipped classroom” model in improving Arabic reading skills among 5th-grade B students at Madrasah Diniyah Darul Muhajirin. The method employed a quasi-experimental nonequivalent control group design. The sample comprised 60 students, divided into an experimental and a control class. Data collection techniques included oral tests, pretest and posttest written assessments, questionnaires, and observations. The data analysis technique uses SPSS assistance. The results showed an increase in the experimental class's average posttest score to 85.5, compared with the pretest score of 74.8. Meanwhile, the control class did not show a significant increase. The result of the t-test (Sig. 2-tailed) is 0.000. Since the calculated t-value is greater than the critical t-value at the 1% significance level (2.392) and the 5% significance level (1.671), the null hypothesis (H₀) is rejected. The alternative hypothesis (Hₐ) is accepted. These findings suggest that the